Validation of a radiographic scoring system for haemochromatosis arthropathy. Issue 12 (2nd August 2010) - Dallos, Tomáš; Sahinbegovic, Enijad; Aigner, Elmar; Axmann, Roland; Schöniger-Hekele, Maximilian; Karonitsch, Thomas; Stamm, Tanja; Farkas, Martin; Karger, Thomas; Cavallaro, Alexander; Stölzel, Ulrich; Keyßer, Gernot; et al.
Abstract : Background: Arthropathy is one of the earliest and most common manifestations of hereditary haemochromatosis with a significant impact on quality of life. Although its radiographic features are well known, there is no assessment tool for their evaluation. Objective: To develop and validate a novel scoring system for the evaluation of radiographic features of haemochromatosis arthropathy. Methods: A dichotomous scoring system assessing four radiographic features of haemochromatosis arthropathy and a 4-grade scale reflecting severity of radiographic change have been developed. Standard radiographs (hand, wrist, knee and ankle) of 170 subjects (116 male, 54 female) with genetically confirmed haemochromatosis and laboratory signs of iron overload were assessed by three readers and construct validity, feasibility and cross-sectional reliability (intrareader and inter-reader) were assessed. Results: Intrareader and inter-reader reliability as assessed by percentage pairwise agreement and Cohen's weighed κ were good to excellent for most features and locations evaluated. Radiographic scores correlated well with clinical parameters (bony swollen joint count, hand function and physician's global health assessment; Pearson's correlation, r 2 =0.18–0.62, p<0.0001). A complete set of radiographs took 3.4±1.2 (mean±SD) min to be assessed. An atlas of characteristic radiographic features was compiled. Conclusion: A feasible and reliable radiological assessment tool for the evaluation of haemochromatosis arthropathy has been validated and an atlas of characteristic radiographic features provided.